Synthesis and characterisation of chemical bath deposited TiO2 thin-films - Manurung, P.; Putri, Y.; Simanjuntak, W.; Low, It Meng (Elsevier Science Ltd, 2013)
A series of titania thin films was prepared by chemical bath deposition (CBD) of TiCl3 on indium tin oxside (ITO) glass at room temperature, followed by calcinations at 500°C for 4h. The effect of cyclic deposition on phase composition, microstructure and electrical resistivity of TiO2 thin films was characterised using X-ray diffraction, scanning electron microscopy and four-point probe respectively. Results showed that TiO2 films produced by single deposition cycle were amorphous. In contrast, those produced by 5 and 6 deposition cycles were partly amorphous and partly crystalline with the formation of rutile. Both the film thickness and electrical resistivity increased with an increase in the number of deposition cycles.